Efficiency assessment of electricity generation in China using meta-frontier data envelopment analysis: Cross-regional comparison based on different electricity generation energy sources. (January 2022) - Xiao, Qin-Wen; Tian, Ze; Ren, Fang-Rong
Abstract: China is the world's largest electricity producer and consumer, and the healthy development of the electricity industry contributes to its economic growth and social stability. Yangtze River Economic Belt (YREB) and non-YREB are two major economic engines of great strategic significance for China with distinct differences in the external development environment of their power industry. A cross-regional comparison of electricity generation efficiency in China is meaningful to obtain a more accurate understanding of the power generation efficiency of YREB and non-YREB, but there is currently no literature in this area as well as none for comparing electricity generation efficiency between different energy sources. Therefore, this research uses the meta-frontier epsilon-based measure (EBM) data envelopment analysis (DEA) model to calculate the efficiency of different electricity generation energy in YREB and non-YREB for the period 2013–2017. The empirical results show that: 1) YREB's electricity industry has higher electricity generation efficiency than non-YREB's, and the efficiency gap is continuing to widen; 2) YREB's average thermal electricity generation efficiency is higher than non-YREB's; 3) YREB's clean energy power generation efficiency is always higher than non-YREB's; 4) regional differences in YREB are smaller than those in non-YREB; and 5) the efficiency value of clean energy power generation is lower than that of thermal power generation. From our analysis results, this paper presents some policy recommendations. Highlights: Using meta-frontier EBM to measure the electricity generation efficiency in YREB and non-YREB. YREB's electricity industry has a higher electricity generation efficiency than non-YREB's. China's Clean energy's electricity generation efficiency is lower than thermal power's.